Adsorption of Cu(II), Zn(II) and Fe(II) using Chengal sawdust - Nor Hidayah, Ahmad Nordin (2012)
Adsorption of heavy metals by sawdust,an alternative utilization of waste,chosen to investigate the effectiveness of using sawdust to remove heavy metal ions from aqueous solutions for the adsorbent’s economical feasibility and availability in large quantity.In this study,Chengal tree sawdust,an inexpensive material, were investigated as an adsorbent for the removal of Cu(II), Zn(II) and Fe(II) ions from aqueous solutions using batch techniques.The purpose of this research is to investigate the potential of sawdust as natural low cost adsorbent to adsorb Cu(II),Zn(II) and Fe(II) heavy metal ions by the variation of solution pH, contact time,initial concentration and adsorbent dosage.The adsorbent was prepared by collecting the Chengal sawdust, dried and ground the sawdust using grinder and mechanical sieve to specify the adsorbent to certain size.Adsorbate were prepared by diluting 250 mg/L of stock heavy metal solutions then used for testing the effect of removal of the heavy metal ions.0.5g of sawdust as adsorbent with 100 ml adsorbate was kept constant for this experiment where the adsorbate solution varied in pH2 to 10,using concentrated 0.1M NaOH and 0.1M HCl to change pH and put in a orbital shaker,operated at 150rpm for 145minutes.For variation in contact time,the solution was set on the shaker for different sets of time interval 20minutes from minute 5 until minute 145 at constant 150rpm and 25˚C,with adsorbate concentration of 250mg/L.Initial adsorbate solution concentration of 250 mg/L was used with adsorbent sample varying in weight, 0.1g to 0.5g,set on shaker at constant 150 rpm and 25˚C.Adsorption process using Chengal sawdust was found to be suitable at pH4.Kinetic studies were conducted where both pseudo-first order and pseudo-second order yield values of R² from 0.6964 to 0.9453 and from 0.9995 to 1.0 for each order.Adsorption isotherms were described by both Langmuir and Freundlich isotherms. Langmuir equation was found to represent the equilibrium data for adsorption of Cu(II),Zn(II),and Fe(II) using Chengal sawdust (0.9360< R² <0.9905),and the maximum adsorption capacity was highest for Cu(II) with 25.71mg/g.